P2.189 What Matters More? Treating Molluscum Contagiosum or Screening For Other Sexual Infections - An Audit of Clinical Practice. (13th July 2013) - Heseltine, R E; Browne, R
Abstract : Background: Molluscum contagiosum (MC) is a common benign viral skin infection seen in children and adults. The mean duration of lesions is 8 months and resolution expected within 18 months. We planned to audit our clinic management of anogenital MC against the UK BASHH guidelines. Methods: All patients with a coded diagnosis of MC between January 2011 - September 2012 were identified; clinical data were collected from electronic patient records and analysed using an Excel database. Results: 96 patients were newly diagnosed with MC (19 female, 77 male); median age 25 (range 17–48) years. 15% always used condoms and 22% never; the rest mainly sometimes. 76% (72) had 1–2 partners in the preceding 3months. 3 patients were already known to be HIV positive. 96% (92) were offered STI screening and 88 screened. 92% were treated with cryotherapy, 2% podophyllotoxin +/- cryotherapy and 4% conservatively. 45% of cryotherapy patients re-attended, the rest did not. The median number of clinic visits required overall was 1 (range 1–10) but 3 for cryotherapy reattenders. 13 patients had concurrent STIs (prevalence 15%); Chlamydia (7), genital warts (5) and HSV (1). 6 patients with Chlamydia were aged < 25 years. Conclusion: The high prevalence of STIs emphasises the need to screen all patients with anogenital MC. We fell slightly short of the BASHH target of 100% screened for STIs. MC was mainly actively managed with clinic based treatments which have implications in terms of staff resources and patient's need to re-attend for a potentially self limiting condition. A clinical trial has demonstrated comparable efficacy with Imiquimod and cryotherapy; the former slower to work but fewer side effects. Conservative management could lead to autoinoculation and sexual transmission. Selected informed patients could be offered conservative management and home-based therapies can be offered prior to cryotherapy.